Peran BMT Al Makmur Dalam Mewujudkan Ketahanan Ekonomi Keluarga Miskin - Mariko, Suhatri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to analyze the role of the Sharia Microfinance Institution BMT Al Makmur in efforts to realize the economic resilience of poor families. This type of research is field research with a qualitative descriptive approach. The data sources are BMT Al Makmur Leaders and Murabahah Financing Customers. Data collection techniques are interviews and documentation. Data analysis techniques are carried out through data reduction, data display and conclusion drawing. The results showed that the presence of BMT Al Makmur as a Sharia Microfinance Institution has had a positive impact on realizing economically resilient families by managing family economic risks for the future. Through murabahah financing channeled for the purpose of purchasing gold which is used as a medium for saving money by customers, because it is believed that investment through gold is a safe and profitable investment category. The gold is used as a reserve to anticipate and fulfill needs for the future, such as the need for children's education costs, and to make their own homes.